2010
DOI: 10.1038/ja.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of two old antibiotics against clinical isolates of methicillin-resistant Staphylococcus aureus

Abstract: The objective of this paper was to investigate the in vitro effects of fusidic acid combined with fosfomycin against methicillin-resistant Staphylococcus aureus (MRSA). In all, 196 MRSA strains isolated from three clinical specimens of human infections from hospitals in China were used in this study. The checkerboard method was used to determine whether combinations act synergistically against these strains. The susceptibility results for fusidic acid and fosfomycin were interpreted according to the guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Finally, fosfomycin was bacteriostatic against vancomycin-resistant enterococci (VRE) in urinary stents biofilms. The MIC 90 of VRE strains increased from 64 mg/liter in planktonic cultures to 128 mg/liter in biofilm cultures (36).…”
Section: Activity In Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, fosfomycin was bacteriostatic against vancomycin-resistant enterococci (VRE) in urinary stents biofilms. The MIC 90 of VRE strains increased from 64 mg/liter in planktonic cultures to 128 mg/liter in biofilm cultures (36).…”
Section: Activity In Biofilmsmentioning
confidence: 99%
“…Table 2 shows the susceptibility of contemporary bacteria to fosfomycin from the larger studies published from 2010 onwards (36,56,57,61,. Regarding Gram-positive bacteria, contemporary studies showed that fosfomycin is active against the majority of S. aureus strains (Ͼ90%), including MRSA, as well as coagulase-negative staphylococci (CoNS) (36,56,61,72,75,82,83,87,88,90). However, one study reported that only 33.2% of MRSA strains were susceptible to fosfomycin (90).…”
Section: Susceptibility Reports (Gram-negative and Gram-positive Isolmentioning
confidence: 99%
See 1 more Smart Citation
“…18 MRSA is considered an important problem in both hospital-and community-acquired infections. 19 In a study conducted by Falagas et al, 20 129 of 130 (99.2%) MRSA isolates and 745 of 961 (77.5%) MRCoNS isolates were susceptible to fosfomycin.…”
Section: 13mentioning
confidence: 99%
“…Tek ba şı na fu si dik asit te da vi si sı ra sın da di renç geli şe bil di ği bi lin mek te dir. 8 Bu ça lış ma da, has ta ne en fek si yon la rı na neden olan MRSA, MRKNS ve en te ro kok izo lat ların da; li ne zo lid, dap to mi sin, te i kop la nin ve fu si dik asit (en te ro kok ha riç) an ti bi yo tik le ri için MİK de ğer le ri nin be lir le ne rek du yar lı lık la rı nın kar şı laş tı rıl ma sı amaç lan mış tır.…”
unclassified